2022
DOI: 10.1111/1759-7714.14534
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcome after palliative treatment of malignant pleural effusion

Abstract: Background The objective of this nationwide, registry‐based study was to compare the two most frequently used procedures for the palliative treatment of a malignant pleural effusion (MPE) and to evaluate differentiated indications for these two procedures. Methods This was a retrospective observational study based on data of the “PLEURATUMOR” registry of the German Society for Thoracic Surgery. Patients who were documented in the period from January 2015 to November 2021 and had video‐assisted thoracic surgery… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…However, serious complications were uncommon ( 2 ). Reflecting the findings of several other studies, including those by Markowiak et al ( 19 ) and Dilkaute et al ( 20 ), IPC placement drastically reduced the LOS for patients compared to the other more invasive treatment options. The mean duration of hospital stay in our IPC group at initial admission was six days.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, serious complications were uncommon ( 2 ). Reflecting the findings of several other studies, including those by Markowiak et al ( 19 ) and Dilkaute et al ( 20 ), IPC placement drastically reduced the LOS for patients compared to the other more invasive treatment options. The mean duration of hospital stay in our IPC group at initial admission was six days.…”
Section: Discussionsupporting
confidence: 65%
“…This study started from the day of initial admission and hospitalization, in contrast to the time of intervention, which is often used as a starting point in other research articles. This is one reason for the longer total time spans, as opposed to generally shorter time intervals, as seen in the similar articles mentioned above ( 19 ). The longer LOS, apart from IPC placement, was also due to our surgical procedure because we routinely apply a level of suction of 20 cmH 2 O for at least 72 hours after talc pleurodesis.…”
Section: Discussionmentioning
confidence: 80%
“…12,18 Low-performance status and delay between pleural effusion diagnosis and pleurodesis were reported to be statistically significant factors for postoperative mortality. 14,18 Markowiak et al 19 suggested that 30-day mortality (5.8%) was not related to the procedure but to the primary disease.…”
Section: Variablesmentioning
confidence: 99%
“…In the literature, the success rate in patients who underwent VATS talc pleurodesis for MPE was between 76% and 96%. 19,20 Cardillo et al 14 argued that the early-phase VATS talc pleurodesis procedure increased the chance of success. Meanwhile, Cobanoglu et al 5 suggested that talc pleurodesis is more likely to be successful when MPE is asymptomatic and a low amount of effusion is detected.…”
Section: Variablesmentioning
confidence: 99%
“…For example, surgery and loco-regional chemotherapy are combined in PM management such that, after tumor resection, the pleural cavity is perfused with a cisplatin solution to remove residual malignant cells. However, the procedure per se represents a hazard for the medical team in the operating room, since the solution can leak during the perfusion of thoracic cavity, leading to possible contamination of surfaces and exposure of the surgical team to the antineoplastic drug [7]. Additionally, cisPt as a liquid solution is easily cleared from the application site, thus rapidly decreasing its local effect and exposing other parts of the body to the drug.…”
Section: Introductionmentioning
confidence: 99%